Insider Trading, Investment, and Liquidity: A Welfare Analysis - Bhattacharya, Sudipto; Nicodano, Giovanna (Journal of Finance, 2001)
We compare equilibrium trading outcomes with and without participation by an informed insider, assuming inflexible ex ante aggregate investment choices by agents. Noise trading arises from aggregate uncertainty regarding other agents' intertemporal consumption preferences. The welfare levels of outsiders can thus be ascertained. The allocations without insider trading are not ex ante Pareto efficient, because our model differs from standard ones with negative exponential utility functions and normal returns. We characterize the circumstances under which the revelation of payoff‐relevant information via prices—arising from insider trading—benefits outsiders with stochastic liquidity needs, by improving risk‐sharing among them.